2004
DOI: 10.1074/jbc.m402904200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ID2 Expression by Hypoxia-inducible Factor-1

Abstract: ID (inhibitor of differentiation/DNA binding) proteins, frequently deregulated in advanced human malignancies, can participate in multiple fundamental traits of cancer, such as block of differentiation, increased proliferation, tissue invasiveness, and angiogenesis. We have previously demonstrated that hypoxia decreases expression of neuronal marker genes in neuroblastoma, but induces genes expressed in the neural crest, such as ID2. Because of its involvement in normal neural crest development and its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…We elected to assess UPR activity in a panel predominantly consisting of neuroblastoma cells because the hypoxic downregulation of Id-1, an event dependent on UPR activation, does not occur in several neuroblastoma cell lines (3,28,29). However, our assessment of UPR activity and eIF2B␦ isoform expression was limited to a relatively small number of cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We elected to assess UPR activity in a panel predominantly consisting of neuroblastoma cells because the hypoxic downregulation of Id-1, an event dependent on UPR activation, does not occur in several neuroblastoma cell lines (3,28,29). However, our assessment of UPR activity and eIF2B␦ isoform expression was limited to a relatively small number of cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of ATF-3 was responsible for the transcriptional repression of Id-1. However, previous reports suggested that Id-1 was not down-regulated in the neuroblastoma cells SK-N-BE(2) and SH-5YSY when rendered hypoxic (28,29). We confirmed this observation and noted that, despite a high basal phosphorylation of eIF2␣, ATF-4, ATF-3, and CHOP were not-up-regulated in response to thapsigargin (a calcium ionophore that permeabilizes the ER membrane) or tunicamycin (which leads to the glycosylation of ER proteins) or when rendered hypoxic.…”
mentioning
confidence: 90%
“…1F). Because Id-2 has been demonstrated to be a HIF-1 target in neuroblastoma cells (37), we sought to determine whether Id-1 is also a HIF-1 target. We constructed a lentivirus expressing a shRNA directed against HIF-1␣.…”
Section: Hif-1 Transactivates Id-1 In the Absence Of The Upr-althoughmentioning
confidence: 99%
“…Hypoxia belongs to factors capable to induce in vitro cell differentiation in neuroblastoma cultures [5,7]. Oxygen deficiency directly affects activity of genes responsible for differentiation of neuroblasts [12,14]. The factors stimulating differentiation of neuroblasts exhibit also protective properties during hypoxia and other adverse exposures [7].…”
Section: The Number Of Survived Cells Depended On the Ini-mentioning
confidence: 99%